Evaluation of Aqueous Extracts of Agro-Industrial Waste as Corrosion Inhibitors in a Neutral Saline Medium - M. M. Marques; A. V. C. Braga; F. N. Ferreira; J. S. Gois; C. S. Silva; D. C. B. do Lago; L. F. Senna (Materials Research)
This work investigated the corrosion inhibition of carbon steel in 0.1 mol L-1 Na2SO4 by lyophilized extracts of garlic white peel (GP) and centrifugation residue of Isabel grape juice (CGJ) using gravimetric tests, polarization curves, electrochemical impedance spectroscopy, and scanning electron microscopy. Initially, the DPPH (2,2-diphenyl-picrylhydrazyl) method analyzed the extracts for antioxidant activity. Considering the capacity to scavenge the DPPH free radical (% DPPH consumed), the GP and GJC lyophilized extracts presented values of 12.64 and 8.47, respectively. The inhibition efficiency exceeded 96% and 88% after 24 h of immersion in the saline medium containing 300 mg L-1 of the GP and CGJ, respectively. These results indicate that producing such extracts is an excellent alternative for using these agro-industrial wastes, as they showed promising results as corrosion inhibitors for carbon steel in the corrosive environment studied.